Respiratory Disorders Related to e-Waste Exposure among Workers in the Informal Sector in a Sub-Saharan African City: An Exposed Nonexposed Study - Ablo Prudence Wachinou; Nonvignon Marius Kêdoté; Geraud Padonou; Serge Adè; Joaquin Darboux; Mirlène Tohi; Arnauld Fiogbé; Julius Fobil; Gildas Agodokpessi (Pulmonary Medicine)
Introduction. Exposure to electrical and electronic equipment waste (e-waste) has become a growing health concern. The objective of this study was to measure the effect of exposure to e-waste on respiratory symptoms and on lung function parameters in workers involved in informal recycling activities in Cotonou city, Benin. Methods. This was a cross-sectional study, in which exposed e-waste workers in Cotonou city were randomly selected. A matching nonexposed group based on age and sex was recruited from the general population. Respiratory symptoms were investigated using a questionnaire adapted from the British Medical Research Council’s standardized respiratory questionnaire. Participants underwent lung function test using a portable spirometer (MIR SPIROBANK). Data were analyzed with STATA version 15 software. Results. The overall prevalence of respiratory symptoms in e-waste workers was statistically higher in the exposed group (33.1% vs. 21.6%; p=0.027). Chest tightness (11.8% vs. 2.1%; p=0.003) and breathlessness (6.8% vs. 1.4%; p=0.018) were the most reported symptoms by e-waste workers. Lung function testing showed a higher proportion of disorders among e-waste workers (25.0% vs. 14.9%, p=0.029), with a higher proportion of probable restrictive (10.8% vs. 2.7, p=0.005) and mixed (4.1% vs. 0%, p=0.013) ventilatory disorders. Handling or working with e-waste was found associated with a significant reduction in forced expiratory volume in one second (FEV1) by 0.4 L (95% CI: 0.3-0.6) and forced vital capacity (FVC) by 0.75 L (95% CI: 0.6-0.9) after adjustment for age, BMI, smoking habits, asthma history, and daily income. Conclusion. Work involving e-waste is associated with a higher prevalence of respiratory symptoms and with an increased risk of FEV1 and FVC decline, as well as of lung function impairment, particularly of restrictive disorders. Further studies to better clarify this association are needed. Awareness on this major public health threat should be raised in other sub-Saharan and Asian urban areas.